2012
DOI: 10.1021/cn3000372
|View full text |Cite
|
Sign up to set email alerts
|

Click-Modified Cyclodextrins as Nonviral Vectors for Neuronal siRNA Delivery

Abstract: RNA interference (RNAi) holds great promise as a strategy to further our understanding of gene function in the central nervous system (CNS) and as a therapeutic approach for neurological and neurodegenerative diseases. However, the potential for its use is hampered by the lack of siRNA delivery vectors which are both safe and highly efficient. Cyclodextrins have been shown to be efficient and low toxicity gene delivery vectors in various cell types in vitro. However, to date, they have not been exploited for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
2
2

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 62 publications
5
49
2
2
Order By: Relevance
“…Analysis of SC12CDClickpropylamine-siRNA nanocomplexes in this current study and previous studies has shown that they are capable of forming compact nanocomplexes between 125 and 200 nm in size and are highly cationic in nature using dH 2 O. (16,17,33,34) In addition, previous gel Table 3. SC12CDClickpropylamine-siRNA Nanocomplex Droplet Sizes Generated electrophoresis analysis by our group has also demonstrated that SC12CDClickpropylamine nanocomplexes efficiently encapsulate siRNA at MR > 10.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Analysis of SC12CDClickpropylamine-siRNA nanocomplexes in this current study and previous studies has shown that they are capable of forming compact nanocomplexes between 125 and 200 nm in size and are highly cationic in nature using dH 2 O. (16,17,33,34) In addition, previous gel Table 3. SC12CDClickpropylamine-siRNA Nanocomplex Droplet Sizes Generated electrophoresis analysis by our group has also demonstrated that SC12CDClickpropylamine nanocomplexes efficiently encapsulate siRNA at MR > 10.…”
Section: Discussionsupporting
confidence: 59%
“…SC12CDClickpropylamine-siRNA Nanocomplex Droplet Sizes Generated electrophoresis analysis by our group has also demonstrated that SC12CDClickpropylamine nanocomplexes efficiently encapsulate siRNA at MR > 10. (17) In contrast, this study found that formulation of siRNA nanocomplexes in PBS resulted in marked increases in particle size. This phenomenon has been previously reported for siRNA nanoparticles and did not correlate to a loss in transfection efficiency.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Lipofectamine 2000 ® has been widely investigated for siRNA delivery in PC3 cells [87e89]. Although the toxicity of this cyclodextrin delivery vector has been analysed and reported in other cell lines [35,40,41,85,86], the toxicity in PC3 cells has not been previously investigated and thus an MTT assay was conducted ( Fig. 7(a)).…”
Section: Gene Knockdownmentioning
confidence: 99%